A Survey of Benthic Assemblages of Foraminifera in Tropical Coastal Waters of Pulau Pinang, Malaysia - Fatin Izzati Minhat; Khairun Yahya; Anita Talib; Omar Ahmad (Tropical Life Sciences Research, 2013)
The distribution of benthic Foraminifera throughout the coastal waters of Taman Negara Pulau Pinang (Penang National Park), Malaysia was studied to assess the impact of various anthropogenic activities, such as fishing, ecotourism and floating cage culture. Samples were obtained at 200 m intervals within the subtidal zone, extending up to 1200 m offshore at Teluk Bahang, Teluk Aling, Teluk Ketapang and Pantai Acheh. The depth within coastal waters ranged between 1.5 m and 10.0 m, with predominantly muddy substrate at most stations. Water quality analysis showed little variation in micronutrient (nitrite, NO2; nitrate, NO3; ammonia, NH4 and orthophosphate, PO4) concentrations between sampling stations. Temperature (29.6±0.48°C), salinity (29.4±0.28 ppt), dissolved oxygen content (5.4±0.95 mg/l) and pH (8.5± 0.13) also showed little fluctuation between stations. A total of nine genera of foraminifera were identified in the study (i.e., Ammonia, Elphidium, Ammobaculites, Bigenerina, Quinqueloculina, Reopax, Globigerina, Textularia and Nonion). The distribution of benthic foraminifera was dominated by opportunistic groups that have a high tolerance to anthropogenic stressors. Ammonia had the highest frequency of occurrence (84.7%), followed by Bigenerina (50%), Ammobaculites (44.2%) and Elphidium (38.9%). The Ammonia-Elphidium Index (AEI) was used to describe the hypoxic condition of benthic communities at all sites. Teluk Bahang had the highest AEI value. The foraminiferal assemblages and distribution in Teluk Bahang, Teluk Aling, Teluk Ketapang and Pantai Acheh showed no correlation with physical or chemical environmental parameters. Satu kajian terhadap taburan Foraminifera bentik di sekitar perairan Taman Negara Pulau Pinang, Malaysia telah dijalankan untuk mengkaji kesan aktiviti antropogenik seperti penangkapan ikan, eko-pelancongan dan akuakultur sangkar terapung. Sampel telah dikutip pada selaan 200 m bermula dari zon subpasang surut sehingga jarak 1200 m dari pantai di Teluk Bahang, Teluk Aling, Teluk Ketapang dan Pantai Acheh. Kedalaman perairan berjulat di antara 1.5 m dan 10.0 m, dengan substrat yang berlumpur di kebanyakan stesen. Analisis kualiti air menunjukkan variasi kecil dalam kepekatan mikronutrien (nitrit, NO2; nitrat, NO3; amonia, NH4 dan ortofosfat, PO4) antara stesen kajian. Suhu (29.6±0.48°C), saliniti (29.4±0.28 ppt), kandungan oksigen terlarut (5.4±0.95 mg/l) dan pH (8.5±0.13) juga menunjukkan perubahan kecil antara stesen. Sebanyak sembilan genera Foraminifera telah dikenal pasti dalam kajian ini (Ammonia, Elphidium, Ammobaculites, Bolivina, Quinqueloculina, Reopax, Globigerina, Textularia dan Nonionoides). Taburan Foraminifera bentik didominasi oleh kumpulan oportunis yang mempunyai toleransi tinggi terhadap tekanan antropogen. Ammonia menunjukkan frekuensi kepadatan yang tinggi (84.7%) diikuti oleh Bolivina (50%), Ammobaculites (44.2%) dan Elphidium (38.9%). Indeks Ammonia-Elphidium (AEI) telah digunakan untuk menunjukkan keadaan hipoksik dalam komuniti bentik di setiap lokasi. Teluk Bahang mempunyai nilai AEI yang paling tinggi. Himpunan dan taburan Foraminifera di Teluk Bahang, Teluk Aling dan Pantai Acheh tidak menunjukkan sebarang kolerasi dengan parameter persekitaran fizikal atau kimia.